Alexithymia, anger and psychological distress in patients with myofascial pain: a case-control study - Castelli, Lorys; De Santis, Federica; De Giorgi, Ilaria; Deregibus, Andrea; Tesio, Valentina; Leombruni, Paolo; Granieri, Antonella; Debernardi, Cesare; Torta, Riccardo (Frontiers in Psychology, 2013)
Aims: The aim of this study was to investigate psychological distress, anger and alexithymia in a group of patients affected by myofascial pain (MP) in the facial region. Methods: 45 MP patients (mean (SD) age: 38.9 (11.6)) and 45 female healthy controls (mean (SD) age: 37.8 (13.7)) were assessed medically and psychologically. The medically evaluation consisted of muscle palpation of the pericranial and cervical muscles. The psychological evaluation included the assessment of depression (Beck Depression Inventory – short form), anxiety (State-Trait Anxiety Inventory Form Y), emotional distress (Distress Thermometer), anger (State-Trait Anger Expression Inventory - 2) and alexithymia (Toronto Alexithymia Scale). Results: the MP patients showed significantly higher scores in the depression, anxiety and emotional distress inventories. With regard to anger, only the Anger Expression-In scale showed a significant difference between the groups, with higher scores for the MP patients. In addition, the MP patients showed significantly higher alexithymic scores, in particular in the Difficulty in identifying feelings (F1) subscale of the Toronto Alexithymia Scale-20 (TAS-20). Alexithymia was positively correlated with the Anger Expression-In scale. Both anger and alexithymia showed significant positive correlations with anxiety scores, but only anger was positively correlated with depression. Conclusion: A higher prevalence of depressive and anxiety symptoms associated with a higher prevalence of alexithymia and expression-in modality to cope with anger was found in the MP patients. Because the presence of such psychological aspects could contribute to generate or exacerbate the suffering of these patients, our results highlight the need to include accurate investigation of psychological aspects in MP patients in normal clinical practice in order to allow clinicians to carry out more efficacious management and treatment strategies.